Aquaporins Contribute to ABA-Triggered Stomatal Closure through OST1-Mediated Phosphorylation. Issue 7 (10th July 2015) - Grondin, Alexandre; Rodrigues, Olivier; Verdoucq, Lionel; Merlot, Sylvain; Leonhardt, Nathalie; Maurel, Christophe
Abstract : The drought-induced hormone abscisic acid increases guard cell water permeability by activating a specific aquaporin, and thereby promoting stomatal closure, in a mechanism involving a protein kinase. Abstract: Stomatal movements in response to environmental stimuli critically control the plant water status. Although these movements are governed by osmotically driven changes in guard cell volume, the role of membrane water channels (aquaporins) has remained hypothetical. Assays in epidermal peels showed that knockout Arabidopsis thaliana plants lacking the Plasma membrane Intrinsic Protein 2;1 (PIP2;1) aquaporin have a defect in stomatal closure, specifically in response to abscisic acid (ABA ). ABA induced a 2-fold increase in osmotic water permeability ( P  f ) of guard cell protoplasts and an accumulation of reactive oxygen species in guard cells, which were both abrogated in pip2;1 plants. Open stomata 1 (OST1)/Snf1-related protein kinase 2.6 (SnRK2.6), a protein kinase involved in guard cell ABA signaling, was able to phosphorylate a cytosolic PIP2;1 peptide at Ser-121. OST1 enhanced PIP2;1 water transport activity when coexpressed in Xenopus laevis oocytes. Upon expression in pip2;1 plants, a phosphomimetic form (Ser121Asp) but not a phosphodeficient form (Ser121Ala) of PIP2;1 constitutively enhanced the P  f of guard cell protoplasts while suppressing its ABA -dependent activation and was able to restore ABA -dependent stomatal closure in pip2;1 . This work supports a model whereby ABA -triggered stomatal closure requires an increase in guard cell permeability to water and possibly hydrogen peroxide, through OST1-dependent phosphorylation of PIP2;1 at Ser-121.